Undetectable = Untransmittable (U = U): insights from people living with HIV attending health facilities in Rwanda - Pierre Gashema; Felix Ndahimana; Eric Saramba; Tumisime Musafiri; Etienne Ishimwe; Patrick Gad Iradukunda; Angelique Ingabire; Vedaste Masengesho; Sam Kanyesigye; Nadine Rujeni; Muhayimpundu Ribakare; Claude Mambo Muvunyi; et al. (BMC Public Health)
Abstract Background Rwanda has made remarkable progress in scaling up HIV testing, treatment, and healthcare services. Recent data show that 95% of people living with HIV (PLWH) were aware of their status, 97.5% of them are on antiretroviral therapy (ART), and 98% of those who are on treatment have achieved viral suppression. Importantly, growing body of evidence supports the Undetectable = Untransmittable (U = U) concept, affirming that PLWH who maintain an undetectable viral load do not transmit HIV to their sexual partners. This pivotal breakthrough in HIV care has transformed public health strategies and stigma reduction efforts. This study aimed to explore the perspectives of PLWH on the U = U concept in health facilities in Rwanda. Methods An exploratory qualitative study was conducted at three purposively selected health facilities in Rwanda from December 1 to 30, 2023. An interview guide was used to collect data, and data saturation was reached after enrolling 43 PLWH. The data was analyzed using conventional thematic analysis. Results The majority of participants demonstrated good knowledge of HIV transmission, with the U = U concept being particularly well-understood among discordant couples and individuals who have been on treatment for over 10 years. Three themes emerged from the analysis: [1] comprehensive knowledge of HIV transmission among PLWH; [2] reasons for disclosing HIV status and linking to care; and [3] acceptability of the U = U concept. Conclusion Our findings highlight the necessity for broader dissemination of the U = U concept across all PLWH subpopulations. Further research is essential to better understand the challenges faced by PLWH, which is critical for achieving the UNAIDS goal of ending the HIV/AIDS epidemic by 2030.